Answer:
The solution to the system of equation is (-10, -7)
Step-by-step explanation:
To determine the solution to the system of equations below, we will follow the steps below:
y = two-fifths x minus 3 and x = –10
y =
- 3------------------------------------------------------(1)
x = -10
substitute x=-10 into equation (1)
y= 2(-10)/5 - 3
Simplify to get the value of y
y = -20/5 - 3
y = -4-3
y=-7
The standard way of writing solution to a system of equation is (x,y)
Thus x= -10 and y = -7
Hence the solution to the system of equation is (-10, -7)